The Effectiveness of Using Virtual Laboratories in Improving Numeracy Literacy in Physics Practicals - Rindi Sartika Dwi Oktari; Almira Erika Putri; Febby Apriani (Indonesian Publication Center, 2026)
This study aims to analyze the effectiveness of using virtual laboratories in improving numeracy literacy in physics learning through a literature review approach. The background of this study is based on the importance of laboratory activities in physics learning, which are often constrained by limited facilities, time, and safety factors. The method used is a literature study by analyzing six relevant scientific articles published between 2016 to 2025, obtained from Google Scholar and accredited national journals. The analysis was conducted by identifying research methods, variables, and key findings of each study. The results indicate that the use of virtual laboratories consistently improves students’ learning outcomes, science process skills, learning motivation, and conceptual understanding. In addition, virtual laboratories support the development of numeracy literacy through activities such as measurement, data analysis, and interpretation of experimental results. Although it has limitations in psychomotor aspects, virtual laboratories remain effective as an alternative or complement to real laboratory practices. Therefore, it can be concluded that virtual laboratories are an effective and innovative learning medium in enhancing numeracy literacy in physics education.